PENGARUH DIMENSI KUALITAS LAYANAN TERHADAP KEPUASAN PASIEN RAWAT INAP DI RUMAH SAKIT UMUM DAERAH MOROWALI - SULVIANDANI, SULVIANDANI (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2018)
The objective of this research is to find out the effect of service quality physical evidence, reliability, responsiveness, assurance and empathy on patients statisfaction in morowali regional hospital. The research problem is whether the quality of service consists of physical evidence, reliability, assurance, responsiveness and empathy simultaneously and partially significan effect on patients satisfaction in morowali regional general hospital. To prove the hypothesis, the researcher used multiple linear regression analysis tool. The sample draw by accidental sampling technique, where anyone who meet at the location of the research direcly determined as a sample if they are suitable as a source of data, data were collected distribution of questionnaires. To prove the hypothesis simultaneously uses the F test while to prove each hypothesis variable uses t teste.